Pendampingan Berkelanjutan dan Pelatihan Penyusunan “Sustainability Company Profile” UMKM Toko Roti LindaYes - Sugi Suhartono; Carmel Meiden; Yustina Triyani; Stefany Natasha Adrea; Maria Katharina Sare (Jurnal Abdimas Perbanas, 2022)
Company profile is information about the company that is explained in a concise, clear and valid manner and is intended to increase the trust of potential investors and clients. Company profile is not just information showing location and contact information. Company profile shows potential investors, partners and potential consumers regarding the goods and/or services offered by the company. The Covid-19 pandemic that began to spread in Indonesia starting in March 2020 has had many impacts on business actors, especially Micro, Small and Medium Enterprises (MSMEs). Not a few business actors have gone out of business and were forced to stop their business due to the impact of the Covid-19 pandemic. In connection with the above, the Community Service Team (PkM) of the Accounting Study Program, the Kwik Kian Gie Institute of Business and Informatics (IBIKKG) carried out community service activities, to provide training and assistance in the preparation of a Sustainability Company Profile. This training and mentoring in the context of compiling a Sustainability Company Profile was held for MSME entrepreneurs in the East Jakarta Small Industry Center (PIK), especially the LindaYes Bakery. The purpose of this PKM activity is to help provide understanding to MSME entrepreneurs in East Jakarta PIK, especially LindaYes Bakery in compiling a sustainable company profile. Keywords: Company Profile, Sustainability